An intercomparative study of the effects of aircraft emissions on surface air quality. Issue 15 (5th August 2017) - Cameron, M. A.; Jacobson, M. Z.; Barrett, S. R. H.; Bian, H.; Chen, C. C.; Eastham, S. D.; Gettelman, A.; Khodayari, A.; Liang, Q.; Selkirk, H. B.; Unger, N.; Wuebbles, D. J.; et al.
Abstract: This study intercompares, among five global models, the potential impacts of all commercial aircraft emissions worldwide on surface ozone and particulate matter (PM2.5 ). The models include climate‐response models (CRMs) with interactive meteorology, chemical‐transport models (CTMs) with prescribed meteorology, and models that integrate aspects of both. Model inputs are harmonized in an effort to achieve a consensus about the state of understanding of impacts of 2006 commercial aviation emissions. Models find that aircraft increase near‐surface ozone (0.3 to 1.9% globally), with qualitatively similar spatial distributions, highest in the Northern Hemisphere. Annual changes in surface‐level PM2.5 in the CTMs (0.14 to 0.4%) and CRMs (−1.9 to 1.2%) depend on differences in nonaircraft baseline aerosol fields among models and the inclusion of feedbacks between aircraft emissions and changes in meteorology. The CTMs tend to result in an increase in surface PM2.5 primarily over high‐traffic regions in the North American midlatitudes. The CRMs, on the other hand, demonstrate the effects of aviation emissions on changing meteorological fields that result in large perturbations over regions where natural emissions (e.g., soil dust and sea spray) occur. The changes in ozone and PM2.5 found here may be used to contextualize previous estimates of impacts of aircraft emissions on human health. Key Points: All‐altitude aircraft emissions in five models estimate an increase in 2006 surface‐layer ozone of 0.3 to 1.9% and PM2.5 by −1.9 to 1.2% Modeled O3 and PM2.5 response to aircraft is greatly affected by the inclusion of feedbacks between aircraft emissions and meteorology While some models show much of the surface‐layer perturbations stem from emissions >1 km, they are minor compared with perturbations aloft Plain Language Summary: This study uses five global atmospheric computer models to estimate the effects of global aircraft emissions on surface air quality by tracking changes in ozone and small particles. While each model uses different modeling techniques, they are harmonized with identical input in order to resolve the somewhat conflicting results of previous studies. The results indicate that all‐altitude 2006 commercial aircraft increase global, annual surface ozone by 0.3 to 1.9% and small particulate matter by −1.9 to 1.2%. While the models show general agreement in the ozone response, the response to small particles varies significantly depending on whether models simulate two‐way chemistry/meteorology "feedbacks" (i.e., meteorology affects emissions and emissions affect meteorology) or one‐way (meteorology affects emissions, but meteorology remains the same in simulations with and without aircraft). In models with feedbacks, most of the change to surface particles comes from changes to natural background particles (from sea spray and soil dust), and not aviation directly. This study helps explain the reasons for disagreement in previous studies and emphasizes the need to further investigate the effects of feedbacks in atmospheric models.